(untitled) (International Journal of Food and Nutritional Sciences, 2021)
How to coexist with diversity is one of the biggest problems democracies face. Growing worldwide migration and globalization have brought new possibilities and difficulties for schools to embrace and learn from superdiversity. However, superdiversity and democratic education are not specifically highlighted in the present policy frameworks and instructional approaches. This research investigates the responses of twenty-four teachers (n = 24) from four superdiverse secondary schools in Aotearoa, New Zealand, to the increasing levels of cultural, linguistic, and religious variety in their classes. The paper shows how Dewey’s philosophy of learning by living together with difference, prioritizing shared interests, and developing a socio political awareness of inequalities provides important insights for democratic education by looking at empirical evidence from teacher practices. The research serves as an example of how crucial it is to acknowledge the complexity of relationships in superdiverse situations and the important role educators can play in fostering inclusive classroom environments where democracy may be experienced and learnt. It also emphasizes how educators themselves may go on a path to create pedagogical methods that are more inclusive, justice-focused, and supportive of Indigenous and ethnic minority communities in their classrooms.